Victory through defence: Employers’ policy preferences and success in the industrial democracy reform process in Finland, 1960s–1970s - Wuokko Maiju; Fellman Susanna; Kärrylä Ilkka (Sage, 2022)
This article analyses the Finnish employers’ policy preferences, strategies and success in the industrial democracy (ID) reform process of the 1960s–1970s. The article establishes the employers’ hierarchy of preferences, evaluates how successful they were in realising their objectives, and discusses the strategic choices and contextual factors behind their successes and losses. The article engages with scholarly discussions about interest groups’ policy preferences and success and emphasises the multifaceted nature and the temporal dimension of success. A sufficiently long timeframe is often necessary in order to assess the eventual winners and losers of a policy process, as well as the degrees of success attained by actors.